Where does she find the time? Essays on women and work in two Southeast Asian countries - Gallaway, Julie H., author; Bernasek, Alexandra, advisor; Mushinski, David, committee member; Jianakoplos, Nancy, committee member; Charlton, Sue Ellen, committee member (Colorado State University. Libraries, 2001)
This research is motivated by the need to examine the constraints facing women in their labor force participation. Studying women's access to income is important because various studies have found women spend a larger proportion of their income on goods and services that benefit the household than men spend. These essays consider the labor force participation decision of women in Malaysia and Indonesia with three different approaches: (1) examining the effects of receiving past maternity leave on current labor force participation, (2) disaggregating the decision to work by distinguishing between formal and informal sector employment, and (3) investigating the tradeoff between time spent in market work and housework. Chapter 2 examines a law designed to make labor market participation more compatible with a woman's family responsibilities by estimating how current labor force participation and earnings have been affected by receiving maternity leave from a prior employment. While the effect on earnings is inconclusive, results from the probit model indicate that past recipients of maternity leave are more likely to be current labor force participants than other women. Chapter 3 considers whether the labor force participation decision is appropriately modeled as a choice between two options: to work or not to work. The results from a multinomial logit model confirm the decision between formal and informal sector employment is distinct. The model suggests higher education decreases the probability and the presence of young children increases the probability of informal sector employment. Chapter 4 investigates the tradeoff between a woman's time spent in market production and housework. Results from a tobit model suggest the wives who participate in the labor market are unable to decrease their time in housework by an equivalent amount, thereby increasing their total time in productive activities. Additionally, the evidence from Chapters 3 and 4 leads us to reject the common preferences model of decision-making for these households because the effect of unearned income on the wife's labor force behavior depends on whether the husband or wife received it.
Keywords: women's studies; social conditions and trends; husbands; families and family life; women; wives; households; bias